Research Review on Sensorless Measurement Technology of Permanent Magnet Synchronous Motor - Zhao, Xinkai (International Journal of Mechanical and Electrical Engineering, 2024)
Permanent magnet synchronous motor (PMSM) has the advantages of high torque/inertia ratio, high power factor, fast dynamic response speed and high reliability, and has been widely used in various high-precision AC drive systems. Incremental encoders are usually used to achieve high precision position feedback information for permanent magnet synchronous motors. The use of sensors leads to cost increase, volume increase and reliability reduction. Therefore, the sensorless measurement technology of permanent magnet synchronous motor is more and more concerned and applied by industry and research fields. In this paper, the related literature of sensorless measurement technology of permanent magnet synchronous motor is investigated, and the sensorless measurement technology is comprehensively reviewed. This paper introduces in detail the basic principle of various sensorless measuring techniques, the accuracy of position measurement and the application in the type of permanent magnet synchronous motor. In this paper, the concept of speed pole logarithm ratio is proposed to divide the speed region, and the initial rotor position, low speed and medium speed non-inductive measurement methods are described and compared. Finally, the non-inductive measurement accuracy of permanent magnet synchronous motor is summarized.